Radiographic measurement of leg-length change in the nonoperative leg during total hip arthroplasty: a potential indicator of imaging error? - Wagler, Justin B; Muir, Jeffrey M; Foley, Kelly A; Paprosky, Wayne G (Hip international, 2023)
Anteroposterior (AP) pelvic radiographs are subject to errors that may cause measurement inaccuracy in total hip arthroplasty (THA). Such errors may be detected by measuring pre- to postoperative leg-length changes in the nonoperative leg, which experiences no physical changes during THA. From AP pelvic radiographs, we measured pre- to postoperative leg-length changes (LLC) in the nonoperative legs of 67 patients who underwent primary THA using the trans-ischial line method. An LLC of 0 mm was observed in the nonoperative leg in only 14 cases (21%). A LLC ⩾ 2 mm was observed in 27% (18/67) of cases, including 13% (9/67) with LLC ⩾ 3 mm and 6% (4/67) with LLC ⩾ 4 mm. A post-hoc analysis used a validated method to measure change in pelvic tilt between pre- and postoperative images and found that changes in pelvic tilt ⩾ 4° in the anterior and posterior directions created apparent lengthening (2.0 ± 1.4 mm,